FIRM LEVEL IMPACT OF FDI: EMPIRICAL EVIDENCE FROM INDIAN AUTOMOBILE INDUSTRY - et. al., Saradhi Gonela (International Journal of Modern Agriculture, 2021)
Many studies have investigated the impact of FDIs on the host economy. Some studies point out that the European capital in the first-wave of globalisation made the United States of America the modern economic power house (Solimano and Watts, 2005). The debate on the advantages and disadvantages of FDI is an ongoing one (Reuber et all 1973, Lall and Streeten 1977). The effect from FDI seems to vary from country to country and for some countries FDI can even adversely affect the growth process (Balasubramanyam et al., 1996; Borensztein et al., 1998; De Mello, 1999; Lipsey, 2000 and Xu, 2000). However, not many studies have concentrated on the impact of FDI at firm level, even though FDI is a firm level phenomenon. This article aims to study the impact of FDI at firm level. For this purpose, Indian automobile industry has been studied by making a comparative analysis between companies with FDI and companies without FDI on two aspects a) total factor productivity and b) DuPont Analysis. Total factor productivity of both the groups was studied over a period of 15 years from 1995-96 to 2009-10 and DuPont Analysis was carried out for a period of 10 years between 2000-01 and 2009-10. The results show that the two groups have similar performance on both the parameters showing that FDI do not have any impact on the performance of the companies.